PROBLEMS OF CERTIFIED TRANSLATION OF POLISH SCHOOL DOCUMENTS - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2012)
The author analyses the problems of translating school documents from Polish into German. At the beginning, he gives the definition for an official document and tries to decide whether school documents can be treated as official documents. Furthermore, he defines what the certified translation of documents is and establishes what kind of documents can be subject to it. As the translation of Polish school documents is not possible if one does not know the system of education in Poland, the author describes it and then he discusses in detail the problems of translating school documents. The most important problems in this respect are as follows: the translation of the proper names of institutions issuing school documents, the translation of vocational titles, degrees, academic degrees and academic titles, the translation of the names of school subjects, and the translation of statements about the level of education and qualifications. Finally, the author analyses terminological problems arising from the differences in education systems in Poland and in the German-speaking countries.